Health Benefits of a 16-Week Whole Food, High Fiber, Plant Predominant Diet among U.S. Employees. Issue 2 (February 2023) - Kelly, Rebecca; Hanus, Amy; Payne-Foster, Pamela; Calhoun, Janet; Stout, Ron; Sherman, Bruce W
Purpose: To assess improvements in eating behaviors and health measures among adults participating in a whole food plant predominant diet, Full Plate Living (FPL) program. Design: Retrospective, post hoc analysis of self-reported 16-week pre-post participant data obtained over a 3 year program period (2017-19). Setting: Wellness offering for employees in Southwest U.S. Subjects: Of 6, 820 enrollees, 4, 477 completed the program, further segmented by generational cohorts. Intervention: FPL program materials and weekly online video lessons. Measures: Baseline and follow-up measures included eating behaviors, self-perceived health status and energy, body weight, and confidence in healthy eating and weight loss. Analysis: Paired t-tests were used to examine changes in eating behaviors and health measures. Mixed-effects models were used to examine whether changes among generational cohorts differed. Results: Significant pre-post improvements were demonstrated for all measures, including servings of fruits (1.54 to 2.34), vegetables (2.05 to 2.87), beans (.63 to .99), and weight loss (3.5) ( P < .001). Self-perceived health and energy values, and confidence in making healthy food choices and losing weight improved ( P < .001). Improvements were observed across generational cohorts ( P < .001). Conclusion: The FPL healthy eating approach has a beneficial impact on health measures across generational cohorts, and may be an effective addition to lifestyle medicine and corporate wellness offerings. Longer-term program evaluation is warranted.